Witch hunt : the story of the greatest mass delusion in American political history - Jarrett, Gregg (Broadside, an imprint of HarperCollinsPublishers, 2019)
"Now that every detail and argument set forth in the #1 New York Times bestseller The Russia Hoax has been borne out by the Mueller report, the author is back with a hard-hitting, well-reasoned evisceration of what may be the dirtiest trick in political history"--